2018 IEEE 15th International Symposium on Biomedical Imaging (ISBI 2018) 2018
DOI: 10.1109/isbi.2018.8363797
|View full text |Cite
|
Sign up to set email alerts
|

Spatially regularized wavelet leader scale-free analysis of fMRI data

Abstract: Slow brain dynamics has received considerable interest in the recent years, with the scale-free paradigm playing a crucial role for analysis of various neuroimaging modalities. However, assessing the role of slow arrhythmic fluctuations requires the use of a large continuum of time scales and thus of long time series, hence raising concerns regarding the use of scale-free tools on fMRI data. Further, scale-free analysis remained so far mostly univariate, that is, voxels are analyzed independently, hence neglec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…By exploiting the time delay stability concept, the authors in Ivanov and Bartsch (2014) and Ivanov et al (2016) quantified the dynamic links among physiological systems and demonstrated a robust relation between the network structure and the physiological states. Moreover, despite numerous studies demonstrating the multi-fractal behavior of various biological processes (Goldberger and West, 1987; Stam and de Bruin, 2004; Wink et al, 2008; Bassingthwaighte et al, 2013; Delignières et al, 2016; França et al, 2018; Mukli et al, 2018; Racz et al, 2018a; Wendt et al, 2018), we lack mathematical and algorithmic tools for identifying the causal interdependence structure and the parameters of dynamical models of the type in Eq. (2).…”
Section: Biological (Genomic Proteomic Physiological) Complexity: Mmentioning
confidence: 99%
“…By exploiting the time delay stability concept, the authors in Ivanov and Bartsch (2014) and Ivanov et al (2016) quantified the dynamic links among physiological systems and demonstrated a robust relation between the network structure and the physiological states. Moreover, despite numerous studies demonstrating the multi-fractal behavior of various biological processes (Goldberger and West, 1987; Stam and de Bruin, 2004; Wink et al, 2008; Bassingthwaighte et al, 2013; Delignières et al, 2016; França et al, 2018; Mukli et al, 2018; Racz et al, 2018a; Wendt et al, 2018), we lack mathematical and algorithmic tools for identifying the causal interdependence structure and the parameters of dynamical models of the type in Eq. (2).…”
Section: Biological (Genomic Proteomic Physiological) Complexity: Mmentioning
confidence: 99%